Estimation of scabies prevalence using simplified criteria and mapping procedures in three Pacific and southeast Asian countries - Shu Ki Tsoi; Susanna J. Lake; Li Jun Thean; Alexander Matthews; Oliver Sokana; Mike Kama; Salvador Amaral; Lucia Romani; Margot Whitfeld; Joshua R. Francis; Susana Vaz Nery; Michael Marks; et al. (BMC, 2021)
Abstract Background Scabies causes considerable morbidity in disadvantaged populations. The International Alliance for the Control of Scabies (IACS) published consensus criteria in 2020 to standardize scabies diagnosis. However, these criteria are complex, and a WHO informal consultation proposed simplified criteria for mapping, to identify regions of high prevalence as targets for mass drug administration. We aimed to investigate the accuracy of simplified criteria in determining scabies prevalence, compared to the 2020 IACS criteria. Methods We obtained data relating to demographics, relevant history and skin lesions from all-age prevalence surveys from Fiji (n = 3365) and Solomon Islands (n = 5239), as well as school-aged children in Timor-Leste (n = 1043). We calculated prevalence using the 2020 IACS criteria and simplified criteria and compared these disease estimates. Results There was no significant difference in the pooled prevalence using the two methods (2020 IACS criteria: 16.6%; simplified criteria: 15.6%; difference = 0.9, [95% CI -0.1, 2.0]). In Timor-Leste, the prevalence using simplified criteria was lower (26.5% vs 33.8%). Simplified criteria had a sensitivity of 82.3% (95% CI 80.2, 84.2) and specificity of 97.6% (95% CI 97.2, 97.9) compared to the 2020 IACS criteria. Conclusions The scabies prevalence estimation using simplified criteria was similar to using the 2020 IACS criteria in high prevalence, tropical countries. The prevalence estimation was lower in the school-based survey in Timor-Leste. Mapping using simplified criteria may be a feasible and effective public health tool to identify priority regions for scabies control. Further work assessing use of simplified criteria for mapping in a field setting should be conducted.